ECONOMIC AND POLITICAL FACTORS AFFECTING CORRUPTION IN DEVELOPING COUNTRIES: AN EMPIRICAL ANALYSIS - Salih, TÜREDİ and ALTINER, Ali (Economics and Statistics Research Journal (ESRJ), 2023)
Corruption is a global problem that affects all countries, but it is more prevalent in developing countries. To design effective policies to control or reduce corruption, it is essential to identify the factors that influence it. This study uses panel data from 56 developing countries for the period 2002-2012 and employs a fixed effects model with Driscoll-Kraay standard errors to estimate the economic and political factors affecting corruption. The empirical results indicate that economic growth, economic freedom, and trade openness reduce corruption, while inflation promotes it. Additionally, democracy and political stability are found to have a reducing effect on corruption. This study contributes to the literature by providing insights into the factors that influence corruption in developing countries and presenting policy recommendations for its prevention and reduction.